Photosynthetic rate and biomass production by inoculation of Scleroderma sp. with different concentrations of NaCl in pecan tree - Sánchez-Ledesma, Judith Abigail; Arreola-Ávila, Jesús Guadalupe; Ávila-Rodríguez, Verónica; García-González, Fabián; Carrasco-Hernández, Violeta; Borja de la Rosa, Amparo (Revista Mexicana de Ciencias Agrícolas, 2022)
The pecan tree [Carya illinoinensis (Wangenh) K. Koch] is one of the fruit trees established in northern Mexico, where there is a considerable area of soils with different degrees of salinity, to which the tree is sensitive. In seedlings inoculated with Scleroderma sp., the effect of NaCl was evaluated at concentrations of 0, 20, 25, 30 and 35 mM, including a control without inoculation and without NaCl. The experiment was carried out at the University Regional Unit of Arid Zones in Bermejillo, Durango, Mexico, under greenhouse conditions. The seedlings were watered twice a week, during 2018. The plants inoculated and under non-saline conditions, showed the highest photosynthesis and transpiration, followed by the control seedlings. The concentration of Na+ in root, stem and leaf was lower in the control and in the inoculated seedlings and without NaCl. The concentration of K in inoculated seedlings and under saline and non-saline conditions was like the control. The k/Na ratio was higher in the control and in the inoculated seedlings and under non-saline conditions and decreased as NaCl concentration increased, particularly in the root. The control seedlings showed higher dry weight in root, stem and leaf than those inoculated with Scleroderma sp. and under salt stress, but it was lower than in those inoculated with the fungus and under non-saline conditions. In seedlings under saline stress of 20 and 35 mM, the decrease in dry weight was 8.5 and 47%, compared to the control. Walnut seedlings inoculated with Scleroderma sp. and under non-saline condition, they showed better physiological response and biomass accumulation and not under saline condition.